Green Human Capital as a Preventive Factor of Climate Anxiety in the Workplace: A Phenomenological Study Among Generation Z Employees - Randika Shafly Fawwaz; Eva Fachria; Reni Nur Arifah (International Journal of Economic and Business Research, 2026)
This study investigates the role of Green Human Capital as a preventive factor in reducing climate related psychological vulnerability among Generation Z employees within contemporary workplace environments. The research applies a qualitative phenomenological design to explore how employees interpret environmental uncertainty, sustainability practices, and organizational responsibility through lived workplace experiences. Twelve participants from technology, manufacturing, and service industries were selected using purposive sampling, while data were collected through semi structured in depth interviews and analyzed using phenomenological thematic analysis. The findings reveal that climate related psychological discomfort emerges alongside increasing environmental awareness and perceived organizational responsibility toward sustainability issues. Green Human Capital contributes to emotional adaptation by strengthening environmental understanding, psychological preparedness, resilience, and constructive meaning formation regarding ecological uncertainty. Organizational sustainability culture further reinforces emotional well being through institutional trust, supportive leadership, transparent sustainability communication, and collective environmental engagement. The study demonstrates that sustainability oriented organizational environments function as emotional ecosystems that strengthen employee security, workplace attachment, and psychological resilience. These findings extend Green Human Capital literature by emphasizing its psychological and organizational significance beyond environmental performance and sustainability management.